PHP Solutions Dynamic Web Design Made Easy - Powers, David; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
This is the third edition of David Powers' highly-respected PHP Solutions: Dynamic Web Design Made Easy. This new edition has been updated by David to incorporate changes to PHP since the second edition and to offer the latest techniques—a classic guide modernized for 21st century PHP techniques, innovations, and best practices. You want to make your websites more dynamic by adding a feedback form, creating a private area where members can upload images that are automatically resized, or perhaps storing all your content in a database. The problem is, you're not a programmer and the thought of writing code sends a chill up your spine. Or maybe you've dabbled a bit in PHP and MySQL, but you can't get past baby steps. If this describes you, then you've just found the right book. PHP and the MySQL database are deservedly the most popular combination for creating dynamic websites. They're free, easy to use, and provided by many web hosting companies in their standard packages. Unfortunately, most PHP books either expect you to be an expert already or force you to go through endless exercises of little practical value. In contrast, this book gives you real value right away through a series of practical examples that you can incorporate directly into your sites, optimizing performance and adding functionality such as file uploading, email feedback forms, image galleries, content management systems, and much more. Each solution is created with not only functionality in mind, but also visual design. But this book doesn't just provide a collection of ready-made scripts: each PHP Solution builds on what's gone before, teaching you the basics of PHP and database design quickly and painlessly. By the end of the book, you'll have the confidence to start writing your own scripts or—if you prefer to leave that task to others—to adapt existing scripts to your own requirements. Right from the start, you're shown how easy it is to protect your sites by adopting secure coding practices.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems